Agricultura urbana e segurança alimentar e nutricional: uma análise do programa hortas comunitárias Manu Manuela no município de Maricá/RJ - Teodoro, Iânia Cássia Silva (2020)
The concept of urban agriculture (UA) is still under construction, however, it is acknowledged that agricultural activities related to food production and preservation of natural resources within urban and periurban spaces are recognized. As a part of the debate on urban agriculture and food and nutrition security, this dissertation presents a systematization of the experience of the Manu Manuela Community Garden Program, in the city of Maricá – a metropolitan region of Rio de Janeiro. The general objective is to identify and analyze the process of implanting community gardens and its contribution to the development of urban agriculture and the strengthening of food and nutritional security in Maricá (RJ). The UA includes food supply, job and income generation, lower expenses with distribution logistics, and contributes to the food and nutritional security of the surrounding residents. This model of agricultural activity presents relevant changes in the social, economic, ecological, political and cultural aspects within the urban space demanding joint actions by governmental, non-governmental organizations, civil society and sometimes, international bodies (COAG - FAO, 2018). To build a food and nutrition security policy for the municipality, the city of Maricá-RJ institutes the municipal law no. 2.804 of 7/3/2018, which establishes the components of the food and nutritional security system (SISAN), according to the principles, guidelines, and definitions established in federal law no. 11.346 of 9/15/2006. This dissertation considers the municipal norms as the theoretical basis, the available documentary research by the Maricá Development Company (CODEMAR), photographic records of the cultivation areas and semi-structured interviews with the key actors in the process of community gardens. The Community Gardens Program was implemented to protect public areas and prevent illegal invasions in the subdivision of the study area. However, local geographic conditions such as flood occurrence because of heavy rain, acidic soil. Another important challenge was the difficulty of keeping urban farmers in the project, as many of them were not residents and had intentions of owning the plots without compromising for cultivation. New calls are made from time to time: as farmers do not demonstrate their dedication to the land, the space is opened for new occupants. The sustainability of the community gardens program requires financial investment for events, training, adequacy of spaces (earthworks, supply of drinking water, addition of fertile land, and liming). Additionally, it depends on more actions and articulations between the government and local farmers to strengthen the communities. urban agriculture activities, thus contributing to better food and nutritional security in Maricá (RJ).